Sex determination in Madagascar geckos of the genus Paroedura (Squamata: Gekkonidae): are differentiated sex chromosomes indeed so evolutionary stable? - Koubová, Martina; Johnson Pokorná, Martina; Rovatsos, Michail; Farkačová, Klára; Altmanová, Marie; Kratochvíl, Lukáš (Chromosome research, 2014)
Among amniote vertebrates, geckos represent a clade with exceptional variability in sex determination; however, only a minority of species of this highly diverse group has been studied in this respect. Here, we describe for the first time a female heterogamety in the genus Paroedura, the group radiated in Madagascar and adjacent islands. We identified homomorphic ZZ/ZW sex chromosomes with a highly heterochromatic W chromosome in Paroedura masobe, Paroedura oviceps, Paroedura karstophila, Paroedura stumpffi, and Paroedura lohatsara. Comparative genomic hybridization (CGH) revealed that female-specific sequences are greatly amplified in the W chromosome of P. lohatsara and that P. gracilis seems to possess a derived system of multiple sex chromosomes. Contrastingly, neither CGH nor heterochromatin visualization revealed differentiated sex chromosomes in the members of the Paroedura picta-Paroedura bastardi-Paroedura ibityensis clade, which is phylogenetically nested within lineages with a heterochromatic W chromosome. As a sex ratio consistent with genotypic sex determination has been reported in P. picta, it appears that the members of the P. picta-P. bastardi-P. ibityensis clade possess homomorphic, poorly differentiated sex chromosomes and may represent a rare example of evolutionary loss of highly differentiated sex chromosomes. Fluorescent in situ hybridization (FISH) with a telomeric probe revealed a telomere-typical pattern in all species and an accumulation of telomeric sequences in the centromeric region of autosomes in P. stumpffi and P. bastardi. Our study adds important information for the greater understanding of the variability and evolution of sex determination in geckos and demonstrates how the geckos of the genus Paroedura provide an interesting model for studying the evolution of the sex chromosomes.
Keywords: Sex Chromosomes; Male; pohlavní chromozomy; karyotypizace; srovnávací genomová hybridizace; hybridizace in situ fluorescenční; fylogeneze; Sex Determination Processes; Phylogeny; heterochromatin; Karyotyping; biologická evoluce; mužské pohlaví; Lizards; ještěři; Animals; ženské pohlaví; Biological Evolution; Heterochromatin; telomery; zvířata; Comparative Genomic Hybridization; In Situ Hybridization, Fluorescence; procesy určující pohlaví; Female; Telomere